2021
DOI: 10.35445/alishlah.v13i2.541
|View full text |Cite
|
Sign up to set email alerts
|

Leader-Member Exchange in Educational Institutions

Abstract: This study is motivated by the lack of reading material related to Leader-Member Exchange (LMX) in educational institutions. LMX studies in Indonesia are more dominant incorporates. The purpose of this study was to determine the study of LMX in educational institutions in Indonesia. This research is library research, the primary source of which is articles from journals. The article was taken from google scholar and eric.go.id search engines with the keywords Leader-Member Exchange. Deductive and inductive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…LMX is conceived as the quality of interpersonal exchange and relationship between a leader and subordinates [ [20] , [21] , [22] , 30 ]. It is an important leadership aspect that influences employee behaviour including their voice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…LMX is conceived as the quality of interpersonal exchange and relationship between a leader and subordinates [ [20] , [21] , [22] , 30 ]. It is an important leadership aspect that influences employee behaviour including their voice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The quality of LMX can be understood from two directions. Hardianto and Sari [ 20 ]suggest a high-quality LMX, characterized by strong friendship, loyalty, respect, professionalism, and contribution; and a poor-quality LMX, distinguished by a lack of friendship, loyalty, professional respect, and contribution. Moreover, the literature suggested multi-factors used to determine whether the quality of LMX is high or low [ 12 , 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition becomes flawlessly logical, so it is a way forward to trigger innovative work behavior (Li, Xue, Li, Chen, & Wang, 2020). Study conducted by (Hardianto & Sari, 2021) and (Chen, Wang, Chang, & Hu, 2008) revealed a relationship between the quality of work-life with OCB.…”
Section:  Introductionmentioning
confidence: 96%
“…The application of leadership style will affect the work behavior of teachers and education staff. Good principal leadership will increase OCB, innovative work behavior, job satisfaction, organizational commitment and teacher work engagement (Hardianto & Sari, 2021).…”
Section:  Introductionmentioning
confidence: 99%